2016
DOI: 10.4172/2329-6925.1000277
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Utility of Circulating Microparticles’ Measurement in Heart Failure Patients

Abstract: Heart failure (HF) continues to have a sufficient impact on morbidity, mortality and disability in developed countries. Growing evidence supports the hypothesis that microparticles (MPs) might contribute to the pathogenesis of the HF development paling a pivotal role in the regulation of the endogenous repair system, thrombosis, coagulation, inflammation, immunity and metabolic memory phenomenon. Therefore, there is a large body of data clarifying the predictive value of MP numerous in circulation among subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 129 publications
(156 reference statements)
0
3
0
Order By: Relevance
“…As mentioned earlier, MPs levels vary with many diseases and therefore could be used for diagnosis (Hugel et al, ). Researchers tried to investigate changes in circulating MPs patterns of expression that can be distinctive to certain phenotypes of disease (Berezin, ). For example, studies by Berezin et al have widely investigated the imbalance between MPs released from apoptotic versus activated endothelial cells, to which has been referred to as “impaired phenotype”, to provide predictive scores for heart failure assessment and predicting cardiovascular risks (Berezin, ; Berezin, Kremzer, Martovitskaya, Samura, & Berezina, ; Berezin, Kremzer, Samura, Berezina, & Kruzliak, ).…”
Section: Clinical Utility Of Mps In Strokementioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned earlier, MPs levels vary with many diseases and therefore could be used for diagnosis (Hugel et al, ). Researchers tried to investigate changes in circulating MPs patterns of expression that can be distinctive to certain phenotypes of disease (Berezin, ). For example, studies by Berezin et al have widely investigated the imbalance between MPs released from apoptotic versus activated endothelial cells, to which has been referred to as “impaired phenotype”, to provide predictive scores for heart failure assessment and predicting cardiovascular risks (Berezin, ; Berezin, Kremzer, Martovitskaya, Samura, & Berezina, ; Berezin, Kremzer, Samura, Berezina, & Kruzliak, ).…”
Section: Clinical Utility Of Mps In Strokementioning
confidence: 99%
“…Researchers tried to investigate changes in circulating MPs patterns of expression that can be distinctive to certain phenotypes of disease (Berezin, ). For example, studies by Berezin et al have widely investigated the imbalance between MPs released from apoptotic versus activated endothelial cells, to which has been referred to as “impaired phenotype”, to provide predictive scores for heart failure assessment and predicting cardiovascular risks (Berezin, ; Berezin, Kremzer, Martovitskaya, Samura, & Berezina, ; Berezin, Kremzer, Samura, Berezina, & Kruzliak, ). These scores have been shown to provide better predictive values when combined with other markers in heart failure patients (Berezin, Kremzer, Martovitskaya, Berezina, & Samura, ).…”
Section: Clinical Utility Of Mps In Strokementioning
confidence: 99%
“…The majority investigations have now addressed to the endothelial cell-derived MPs, which are marker of endothelial dysfunction and cardiovascular death [23,24], while MPs originated from other cells (i.e. red blood cells) have exhibited a relation to severity of atherosclerosis and coronary obstruction [25]. Recent studies have shown that the circulating number of endothelial cell-derived MPs originated from activated or apoptotic cells may be markers with powerful independent predictive value in patients with acute myocardial infarction after PCI, although utility of endothelial cell-derived MP measurement is not strongly determined [26].…”
Section: Introductionmentioning
confidence: 99%